2017
DOI: 10.18311/gjeis/2016/15740
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Green Purchase Intentions: Green Self-Efficacy and Perceived Consumer Effectiveness

Abstract: Purpose: This study aims to combine the literature of consumer behavior and green marketing into a new managerial framework of green motivation. In addition, the present study proposes an original framework to explore the influence of Green Self-Efficacy (GSE) on Green Buying Intentions (GPI) of consumers through the mediating role of Perceived Consumer Effectiveness (PCE). Design/Methodology/Approach: The current study summarizes the literature of four concepts namely green self-efficacy, perceived consumer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 0 publications
8
31
2
Order By: Relevance
“…Further, this research shows that environmental concern affect green purchase intention significantly (H 3 supported); green perceived knowledge influence green purchase intention signifcantly (H 4 supported); and green trust has also a significant effect on green purchase intention. These findings are in accordance with previous findings by Adji and Samuel (2014), Albayrak et al, (2013), Azizan and Suki (2003), Azizan and Suki (2014), Chen and Chang (2012), Chen and Deng (2016), Chen et al, (2015), Harris and Goode (2010), Joshia and Rahmanb (2015), Karatu and Mat (2015), Lam et al, (2016), Lasuin and Ching (2014), Lee (2017), Mobrezia and Khoshtinata (2016), Nazar and Syahran (2008), Schultz (2000), Sharma and Dayal (2016), Sharma and Sharma (2016), and Teng and Wang (2015). It means that if the level of environmental concern, green perceived knowledge as well as green trust are high, the consumers will have a stronger green purchase intention.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, this research shows that environmental concern affect green purchase intention significantly (H 3 supported); green perceived knowledge influence green purchase intention signifcantly (H 4 supported); and green trust has also a significant effect on green purchase intention. These findings are in accordance with previous findings by Adji and Samuel (2014), Albayrak et al, (2013), Azizan and Suki (2003), Azizan and Suki (2014), Chen and Chang (2012), Chen and Deng (2016), Chen et al, (2015), Harris and Goode (2010), Joshia and Rahmanb (2015), Karatu and Mat (2015), Lam et al, (2016), Lasuin and Ching (2014), Lee (2017), Mobrezia and Khoshtinata (2016), Nazar and Syahran (2008), Schultz (2000), Sharma and Dayal (2016), Sharma and Sharma (2016), and Teng and Wang (2015). It means that if the level of environmental concern, green perceived knowledge as well as green trust are high, the consumers will have a stronger green purchase intention.…”
Section: Discussionsupporting
confidence: 93%
“…Green purchase intention is one of the most relevant constructs in green marketing. The antecedents and consequences of this variable has widely been investigated by researchers, among others by Azizan and Suki (2014), Chen and Chang (2012), Chen and Deng (2016), Joshia and Rahmanb (2015), Karatu and Mat (2015), Kong et al, (2014), Lasuin and Ching (2014), Lee (2017), Ma et al, (2018), Mobrezia and Khoshtinata (2016), Moyo and Masuku (2018), Sharma and Dayal (2016), and Sharma and Sharma (2017). According to Chen and Chang (2012), green purchase intention is the possibility for the consumers to purchase certain product that is friendly to the environmental needs.…”
Section: Green Purchase Intentionmentioning
confidence: 99%
“…The results show that PCE plays a critical mediating role between voluntary reduction tourist eco-behaviours, values, and the intention to stay in green hotels. Theoretically, the approach used in this study is similar to several previous studies that examined the role of PCE as a mediating relationship (Saleem et al, 2018; Sharma and Dayal, 2016). These findings seem to reflect the exceptional characteristic of PCE.…”
Section: Discussionmentioning
confidence: 99%
“…In previous literature, perceived consumer effectiveness has been identified by researchers as an important factor in understanding consumers' environmentally friendly purchasing behavior (Dagher and Itani, 2014;Benda-Prokeinová et al, 2017). For example, Sharma and Dayal (2017) found that perceived consumer effectiveness has a positive effect on green purchase intention. This factor has been found to relate directly to consumers' attitudes toward green products and to be an important predictor of purchase intention (Sharma and Foropon, 2019).…”
Section: Cognitive Factorsmentioning
confidence: 99%